2012
DOI: 10.1210/me.2011-1116
|View full text |Cite
|
Sign up to set email alerts
|

Complex Human Glucocorticoid Receptor dim Mutations Define Glucocorticoid Induced Apoptotic Resistance in Bone Cells

Abstract: A mutation in the D-loop of the second zinc finger of the DNA-binding domain of the human glucocorticoid receptor (hGR), A458T (GR(dim)), has been suggested to be essential for dimerization and DNA binding of the GR, and genetically altered GR(dim) mice survive, whereas murine GR knockout mice die. Interestingly, thymocytes isolated from the GR(dim) mice were reported to be resistant to glucocorticoid-induced apoptosis. To further evaluate the dim mutations in glucocorticoid-induced apoptosis, we stably expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 42 publications
5
57
0
Order By: Relevance
“…5C). While GR drives more transcription than GR dim at the WT-selective sites, GR dim compares favorably at the common regions, agreeing with earlier studies demonstrating in vitro activity for GR dim (Adams et al 2003;Meijsing et al 2009;Jewell et al 2012). Mutation of the GR half-site sequence within the common regions destroys GR and GR dim activity, demonstrating that transcriptional activation by monomeric GR requires a half-site motif.…”
Section: Gr Dim Partitions the Gr Cistrome Similarly In Primary Macrosupporting
confidence: 87%
See 2 more Smart Citations
“…5C). While GR drives more transcription than GR dim at the WT-selective sites, GR dim compares favorably at the common regions, agreeing with earlier studies demonstrating in vitro activity for GR dim (Adams et al 2003;Meijsing et al 2009;Jewell et al 2012). Mutation of the GR half-site sequence within the common regions destroys GR and GR dim activity, demonstrating that transcriptional activation by monomeric GR requires a half-site motif.…”
Section: Gr Dim Partitions the Gr Cistrome Similarly In Primary Macrosupporting
confidence: 87%
“…Early interpretations proposed no DNAbinding functions for GR dim (Reichardt et al 1998), but our data show that GR dim occupies a majority of sites comprising the GR cistromes in a primary cell type and native tissue and displays little or no selective binding. Recently, the inability of GR dim to form homodimers has been challenged through forced expression of GFP-or YFP-tagged GR dim and monitoring dimerization by immunoprecipitation (Jewell et al 2012) or a number and brightness assay (Presman et al 2014). We detect little, if any, dimeric occupancy for GR dim , indicating that it interacts with the genome primarily as a monomer under physiological conditions.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Of note, in transient transfection studies it was shown that by the GR dim mutation, dimerisation is not entirely absent (Jewell et al, 2012;Watson et al, 2013;Presman et al, 2014). The residual dimerisation of the GR dim mutant is due to the fact that promoters may engage several dimerisation interfaces of the GR that are still present in the GR dim mutation (e.g., in the LBD) (Savory et al, 2001;Bledsoe et al, 2002;Jewell et al, 2012;Presman et al, 2014).…”
Section: Lessons From Gr Dim Micementioning
confidence: 99%
“…However, this paradigm has been established exclusively from in vitro studies, working mostly with the DBD fragment (8)(9)(10), only using the whole GR protein in rare cases (11,12). The small number of experiments performed in live cells only addresses the entire nuclear population, lacking specific information regarding the GR fraction bound to chromatin (13)(14)(15)(16). Furthermore, these studies were unable to discriminate between dimers or higher oligomeric states.…”
mentioning
confidence: 99%